Oxidation Stability of Colloidal Two-Dimensional Titanium Carbides (MXenes) - Zhang, Chuanfang John; Pinilla, Sergio; McEvoy, Niall; Cullen, Conor P; Anasori, Babak; Long, Edmund; Park, Sang-Hoon; Seral-Ascaso, Andrés; Shmeliov, Aleksey; Krishnan, Dileep; Morant, Carmen; Liu, Xinhua; et al. (Chemistry of materials, 2017)
Two-dimensional (2D) transition metal carbides and nitrides (MXenes) have shown outstanding performances in electrochemical energy storage and many other applications. Delamination of MXene flakes in water produces colloidal solutions that are used to manufacture all kinds of products (thin films, coatings, and electrodes, etc.). However, the stability of MXene colloidal solutions, which is of critical importance to their application, remains largely unexplored. Here we report on the degradation of delaminated-Ti3C2T x colloidal solutions (T represents the surface functionalities) and outline protocols to improve their stability. Ti3C2T x MXene solutions in open vials degraded by 42%, 85%, and 100% after 5, 10, and 15 days, respectively, leading to the formation of cloudy-white colloidal solutionss containing primarily anatase (TiO2). On the other hand, the solution could be well-preserved when Ti3C2T x MXene colloidal solutionss were stored in hermetic Ar-filled bottles at 5 °C, because dissolved oxygen, the main oxidant of the MXene flakes, was eliminated. Under such a recipe, the time constant of the solution was dramatically increased. We have found that the degradation starts at the edges and its kinetics follows the single-exponential decay quite well. Moreover, we performed size selection of the MXene solution via a cascade technique and showed that the degradation process is also size-dependent, with the small flakes being the least stable. Furthermore, a dependence between the degradation time constants and the flake size allows us to determine the size of the nanosheets in situ from UV–vis spectra and vice versa. Finally, the proposed method of storing the MXene colloidal solution in Ar-filled vials was applied to Ti2CT x to improve its stability and time constant, demonstrating the validity of this protocol in improving the lifetime of different MXene solutions.